ANALYSIS OF SOURCES AND USE OF WORKING CAPITAL IN ASSESSING FINANCIAL PERFORMANCE AT PT GARUDA INDONESIA PERSERO (Tbk) - Padang, Enrichus Sampe; Mongan, Benyamin; Mongan, Claudio Julio (Indonesian Journal Of Economy Studies, 2024)
The purpose of this study is to determine and analyze the sources and use of working capital at PT Garuda Indonesia Persero Tbk.The object of this research is PT Garuda Indonesia. The analytical method used in this research is descriptive analysis with a quantitative approach and data analysis used is analysis of balance sheet changes, sources and use of funds, sources and use of working capital and financial ratio analysis. The result of the study indicate that PT Garuda Indonesia Tbk applies the spending principle and can be seen from its working capital which has increased. Judging from the financial ratios, it is good, although there are still some things that are still lacking, but this can be improved with good financial management.Keyword: Working Capital Sources,Working Capital Use,Financial Performance,Financial Ratios